Production of cyclodextrins by CGTase from Bacillus clausii using different starches as substrates - Alves-Prado, H. F. [UNESP]; Carneiro, A. A. J. [UNESP]; Pavezzi, F. C. [UNESP]; Gomes, E. [UNESP]; Boscolo, M. [UNESP]; Franco, C. M. L. [UNESP]; da Silva, R. [UNESP] (Humana Press Inc, 2008)
Cyclodextrins ( CDs) are cyclic oligasaccharides composed by D- glucose monomers joined by alpha- 1,4-D glicosidic linkages. The main types of CDs are alpha-,beta-and gamma-CDs consisting of cycles of six, seven, and eight glucose monomers, respectively. Their ability to form inclusion complexes is the most important characteristic, allowing their wide industrial application. The physical property of the CD-complexed compound can be altered to improve stability, volatility, solubility, or bio-availability. The cyclomaltodextrin glucanotransferase ( CGTase, EC 2.4.1.19) is an enzyme capable of converting starch into CD molecules. In this work, the CGTase produced by Bacillus clausii strain E16 was used to produce CD from maltodextrin and different starches ( commercial soluble starch, corn, cassava, sweet potato, and waxy corn starches) as substrates. It was observed that the substrate sources influence the kind of CD obtained and that this CGTase displays a beta- CGTase action, presenting a better conversion of soluble starch at 1.0%, of which 80% was converted in CDs. The ratio of total CD produced was 0: 0.89: 0.11 for alpha/beta/gamma. It was also observed that root and tuber starches were more accessible to CGTase action than seed starch under the studied conditions.
Keywords: CGTase; cyclodextrin; Bacillus clausii; soluble starch; Corn starch; Cassava starch; sweet potato starch; waxy corn starch